To Build or Not to Build? Capital Stocks and Climate Policy - Elizabeth Baldwin; Yongyang Cai; Karlygash Kuralbayeva (Center for Economic Studies and ifo Institute (CESifo), 2018)
We investigate how irreversibility in “dirty” and “clean” capital stocks affects optimal climate policy, from both theoretical and numerical perspectives. An increasing carbon tax will reduce investments in assets that pollute, and so reduce emissions in the short term: our “irreversibility effect”. As such the “Green Paradox” has a converse if we focus on demand side capital stock effects. We also show that the optimal subsidy increases with the deployment rate: our “acceleration effect”. Considering second-best settings, we show that, although carbon taxes achieve stringent targets more efficiently, in fact renewable subsidies deliver higher welfare when policy is more mild.
Keywords: O44; Q54; Q58; 330; infrastructure; clean and dirty energy inputs; renewable energy; stranded assets; carbon budget; climate change policies; Green Paradox